The Measurement of Utility - Hillinger, C. (Review of Economic Studies, 1969)
Journal Article The Measurement of Utility Get access C. Hillinger C. Hillinger Case Western Reserve University, Cleveland Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 1, January 1969, Pages 111–116, https://doi.org/10.2307/2296348 Published: 01 January 1969 Article history Received: 19 February 1968 Revision received: 15 July 1968 Published: 01 January 1969